Effects of injection of HCG and GnRH on serum progesterone and vitamin E in synchronised cows with prostaglandin F-2 alpha - Naziroglu, M; Cay, M; Aksakal, M; Cetin, H; Kaygusuzoglu, E; Kalkan, C (Scientific Technical Research Council Turkey, 1997)
In this study, we aimed to determinate effect of intramuscular administration of HCG and GnRH on vitamin E and progesterone in cows. Twenty Brown-Swiss cows were used and oestrus of the animals were synchronised by prostaglandin F-2 alpha administration. Following synchronization. all of the animals were divided into two groups ten cows each and blood samples from jugular vein were obtained during first oestrus cycles at two days intervals. At the beginning of second oestrus, first group animals received 1500 IU HCG and second group received 100 mu g GnRH. Following this treatment, blood samples were collected as indicated earlier. Serum from blood samples were obtained and vitamin E and progesterone levels were measured. Correlation and differences between first and second oestrus were determined. There was slightly but insignificant positive correlation between levels of serum vitamin E and progesterone during first cycles in both groups. In addition, the serum progesterone concentrations were slightly decreased and vitamin E levels were slightly increased in HCG administered group. However, progesterone and vitamin E levels in GnRH injected group did not change significantly. But the length of oestrus cycles were increased in the injection of HCG and GnRH. In conlusion, we observed that there was a positive but insignificant correlation between vitamin E and progresterone levels during oestrus cycles of cows. But the levels of vitamin E and progesterone during the oestrus cycles did not affected by administering of HCG and GnRH in cows. However, the length of oestrus cycle were significantly increased by HCG and GnRH administration.
Keywords: vitamin E; progesterone; human chronic gonadotropin (HCG); gonadotrophin releasing hormone (GnRH); oestrus; synchronisation